TEKNOLOGI BALL ROLLING UNTUK MELATIH FIRST BALL PADA ATLET SEPAK TAKRAW NASIONAL - Dani Slamet Pratama; Buyung Kusumawardhana; Setyawan (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
sepak takraw is an achievement sport that uses a throwing system. The throwing tool is designed with a variety of movements based on loading and unloading the ball independently and has different speeds according to training needs. The purpose of using a ball throwing tool is for the coach to sharpen the player's sepak takraw playing skills exclusively on each sepak takraw game technique, providing variations of basic training by directing the ball from anywhere and adjusting the desired speed and strength of the ball's throwing power so that the player can sharpen it. the skill of playing sepak takraw on the field. However, not all educational institutions use a support system for sepak takraw training, due to the lack of available facilities and infrastructure and the unavailability of supporting funds. This research was conducted on national sepak takraw athletes with the aim of making a simple sepak takraw throwing device at minimal cost to assist in the implementation of the sepak takraw Student Activity Unit (UKM). This research uses an interview method with a descriptive Research and Development (R & D) approach to develop a sepak takraw throwing tool. The results of the research show that the development of a sepak takraw throwing device for national sepak takraw athletes can be categorized as suitable for use as training, namely bottom passing, top passing and blocking in the sport sepak takraw. This can be seen from the research results of 93% of material experts, 91% of media experts, and 85% of small scale respondents and 82% of large scale respondents.